DIAGRAMANIA - Rodríguez, Emiliano (Universidad ORT Uruguay, 2018)
The topic of this article, titled Diagrammania, is chronologically situated at the beginnings of the contemporary era, when the figure of the diagram was placed at the position of the complexity-facing tool par excellence in a globalized world. The phenomenon of Diagrammania, which took place in the late twentieth century, showed a place of privilege of this figure as it monopolized a great number of headlines in specialized journals, publications of a more theoretical sort and disclosures of projects of renowned studios. This phenomenon,which spanned no more than a decade but spread on a worldwide scale and involved the main protagonists and personalities -both in the theoretical and practical realms- of contemporary architecture, deserves to be studied in-depth. The reach of it also allows us to assume its validity today. To this end, the objective of this work is to provide tools to precisely define the characteristics of the contemporary diagram and to effectively test the importance of its role in the architectural practice, and thus supporting or refuting, the hypothesis of a place of privilege of the diagram in our discipline.